A Systematic Methodology for Doing Qualitative Research. (March 2021) - Gioia, Denny
The Journal of Applied Behavioral Science is in the enviable position of being a go-to journal for many readers seeking useable insights for solving practical problems in managing modern organizations. A perennial source of such knowledge has been case studies, but case studies have been treated as questionable sources of widely applicable knowledge because they have been assumed to be idiosyncratic and to lack adequate "scientific" rigor. In this brief article, I argue for using a methodological approach to studying single cases that addresses both these thorny problems.